Effects of low intensity blood flow restriction and high intensity resistance training on muscle stiffness - Gözübüyük, Ömer Batın. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2018., 2018)
Blood flow restriction training (BFR) has become a popular training method recently. Both athletic and non-athletic populations prefer BFR over high intensity training (HI) due to the use of much lower loads. Although the mechanical tension of BFR is considered lower than that of HI, the metabolic stress is much higher. It has been shown that imposing high loads to a muscle during training affects stiffness of the muscles acutely. However the long-term effects of HI training on the subjected muscle’s stiffness is not studied extensively. Moreover, it is not known how the BFR training affects this property. We compared the effects of 6 weeks of BFR and HI -elbow flexion- training on stiffness of biceps brachii muscle. Seventeen healthy participants volunteered for the study, randomly divided into BFR (n=8) and HI (n=9) groups. BFR group trained with 30-40% of their 1 repetition maximum (1-RM) and HI group trained with 75-85% of 1-RM. Prior to and at the end of the study, passive stiffness of the biceps brachii was measured with shear-wave elastography (SWE) and Myoton-Pro device. Hypertrophy effects (B-mode ultrasound) and strength gains (1- RM test) were also measured. Training did not induce a significant change of SWE in HI group (13.83 2.49 kPa pretraining, 14.72 3.01 kPa post training) or in BFR group (14.26 3.64 kPa pretraining, 14.69 4.87 kPa posttraining) (p>0.05). Stiffness measured by Myoton device did not change in HI group (202.52 16.42 N/m pretraining, 205.12 18.6 N/m posttraining) or in BFR group (208.92 19.62 N/m pretraining, 206.15 15.52 N/m posttraining)(p>0.05). Both groups improved in terms of hypertrophy (p<0.001) and strength gains (p<0.0001). Our study showed that BFR training did not alter passive mechanical properties of the subjected muscle in the long term, thus providing information regarding the efficacy and safety of BFR training.|Keywords : Occlusive training, elastic modulus, ultrasound, myoton, shear-wave, elastography.
Keywords: Blood flow -- Regulation.; Elastography.; Shear waves.